2014
DOI: 10.1016/j.jcct.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Reduced iodine load with CT coronary angiography using dual-energy imaging: A prospective randomized trial compared with standard coronary CT angiography

Abstract: Background There is concern regarding the administration of iodinated contrast to patients with impaired renal function because of the increased risk of contrast-induced nephropathy. Objective Evaluate image quality and feasibility of a protocol with a reduced volume of iodinated contrast and utilization of dual-energy coronary CT angiography (DECT) vs a standard iodinated contrast volume coronary CT angiography protocol (SCCTA). Methods A total of 102 consecutive patients were randomized to SCCTA (n = 53)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
33
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 13 publications
7
33
1
Order By: Relevance
“…Several studies have recently reported that the radiation dose can be reduced to the 2-4 mSv level in CCTA using DECT. 14,15) Our results have extended this further, with dose reductions of 25-62% compared with all above mentioned radiation levels.…”
Section: Discussionsupporting
confidence: 61%
“…Several studies have recently reported that the radiation dose can be reduced to the 2-4 mSv level in CCTA using DECT. 14,15) Our results have extended this further, with dose reductions of 25-62% compared with all above mentioned radiation levels.…”
Section: Discussionsupporting
confidence: 61%
“…These techniques are, however, invasive and assessment limited to the iliofemoral arteries, excluding imaging of the aortic root which is essential for device selection (34)(35)(36). Another potential technique for contrast dose reduction is using low keV reconstructions on dualenergy CT; while there is published data on low dose coronary/pulmonary CTA with this technique (37,38), there is no published experience with pre-TAVR scanning and one study reported that image quality was impacted (37). Overall, high-pitch ECG-triggered helical imaging is a reliable and reasonable approach for low-contrast dose pre-TAVR scanning and is routinely performed at our institution with a total of 30-40 cc of contrast ( Figure 4).…”
Section: Low Dose Tavr Ctamentioning
confidence: 99%
“…Halliburton and colleagues compared in a clinical setting dual-source and 32-slice CT with regard to radiation exposure, and they showed no difference in radiation doses for coronary imaging between the two modalities (46). Similarly, in a head-to-head prospective randomized clinical trial evaluating 102 patients, DECT based on rapid-kV-switching enabled coronary CTA examinations at dosage levels comparable with contemporary multi-detector CCTA, 2.31 vs. 2.23 mSv, respectively (47). Although no study has evaluated the radiation dose of DECT devices based on double-layer technology for cardiac imaging, presumably these devices will produce similar radiation doses overall to single-energy CT, since there is no double irradiation of tissue to obtain low and high-energy datasets.…”
Section: Radiation Dose Aspects Of Dual-energy Ctmentioning
confidence: 99%
“…Therefore, an optimal difference in contrast attenuation between normally perfused myocardium (high attenuation) and ischemic myocardium is anticipated with low-energy monochromatic imaging, considering the low K-edge of iodine. In a prospective randomized clinical study of 102 patients, Raju et al evaluated the feasibility of DECT associated with reduced iodine load, and they found that monochromatic images at 60 keV provided signal- and contrast-to-noise ratios comparable to SECT coronary angiography with full iodine load, while preserving diagnostic interpretability (47). Interestingly, this was accomplished despite a more than 50% reduction in iodine load for CT angiography with DECT.…”
Section: Iodinated-contrast Dose Requirementsmentioning
confidence: 99%